Proceedings of GeoShanghai 2018 International Conference: Rock Mechanics and Rock Engineering (Springer Singapore, 2018)
This book is the third volume of the proceedings of the 4th GeoShanghai International Conference that was held on May 27 - 30, 2018. This volume, entitled "Rock Mechanics and Rock Engineering" , covers the recent advances and technologies in rock mechanics and rock engineering. These papers are grouped in three categories: (1) Theoretical and numerical study of rock behaviours, (2) Experimental study of rock behaviours, and (3) Applications of rock mechanics and case studies. This volume presents the state-of-the-art theories, methodologies and findings in the related areas. The book may benefit researchers and scientists from the academic fields of rock mechanics and rock engineering, geotechnical engineering, geoenvironmental engineering, transportation engineering, geology, mining and energy, as well as practical engineers from the industry.